STRATEGY OF INDONESIA GOVERNMENT TO MANTAINS PALM OIL MARKET IN INDIA - Glory Yolanda Yahya; Desri Gunawan (Jurnal PIR : Power in International Relations, 2020)
This study aims to determine the factors cause a decrease market share of Indonesia palm oil in India and its implications, and to know the Indonesia government’s strategy maintains the palm oil market in India. The method used is descriptive analysis using theory of competitive adventage diamond model of Michael Porter and Development state theory. The scope of study between 2010 and 2015. The results showed that cause of the decline in the market share of Indonesia palm oil in India due to the application of duty Crude Palm Oil (CPO) is higher than its derivative products in Indonesia, Increased demand for Malaysia palm oil by India and development of palm oil industry in India. The implications of this decline include the loss of potential tax revenue and export volume of palm oil as well as disrupt the Indonesia palm oil industry. Strategy by the Indonesia government is implementing Crude Palm Oil (CPO) Supporting Fund (CSF), Indonesia Trade Promotion Center (ITPC) Chennai (India) and Palm Oil Industrial Cluster. Strategy Indonesia government maintains the palm oil market in India has shown a positive effect. Although some parts are not running perfectly. The government as a stimulant to increase competitiveness of Indonesia palm oil is felt has done its job as it should. Futhermore, this strategy can be continued with evaluation and continuous improvement.